DETERMINATION OF THE BIOACTIVE COMPOSITION AND ANTIMICROBIAL ACTIVITY OF THE AQUEOUS EXTRACT OF WILD BLUEBERRIES COLLECTED FROM KURT DAĞI HIGHLANDS (TRABZON, TÜRKİYE) - Hanife Kara; Salih Özden; Meltem Özden (Sabuncuoglu Serefeddin Health Sciences, 2026)
Blueberries (Vaccinium arctostaphylos L.), which grow naturally in the Black Sea region and are consumed by the local population for their health benefits, are known as a functional food characterized by small, dark purple-blue berries. Considering that the bioactive content and health effects of blueberries may vary depending on the environmental conditions in which they are grown, we aimed to measure the polyphenol and flavonoid contents of blueberries naturally grown on the Kurt Dağı plateau and to determine their antimicrobial activity. A single pooled aqueous extract derived from Vaccinium arctostaphylos fruits (n=1) was prepared: floral samples collected from the Kurt Dağı plateau in August 2024 were dried at 45°C for 24 hours; a 700 mg portion of this sample was dissolved in 25 mL of pure water, and all measurements were performed on the resulting solution. The extraction process and chemical measurements were repeated three times. The total polyphenol (21.041 ± 0.976 µg/g GAE) and flavonoid content (1.733 ± 0.294 µg/g QE) were quantified. Antimicrobial susceptibility testing against three standard reference strains revealed that the pooled extract exhibited moderate-weak inhibitory activity against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922 (MIC: 6.5 mg/mL), whereas only weak inhibitory activity was observed against Pseudomonas aeruginosa ATCC 27853 (MIC: 25 mg/mL). These data indicate that the blueberry population in the region has a significant antimicrobial potential, consistent with its high phenolic content, and can be considered a natural inhibitor of pathogenic microorganisms.